HUBUNGAN ANTARA LITERASI KEBENCANAAN DENGAN KESIAPSIAGAAN MASYARAKAT UNTUK MENGHADAPI BENCANA: ANALISIS KETERKAITAN LITERASI KEBENCANAAN DENGAN KESIAPSIAGAAN BENCANA PADA MASYARAKAT KOTA CIMAHI - Setyo Alif Pradipto; Edwin Rizal; Nuning Kurniasih (Jurnal Perpustakaan dan Informasi, 2026)
Indonesia’s geographic locations surrounded between two major oceans and two major continents brings a number of advantages and disadvantages such as high soil fertility as well as high propensity for tectonic and volcanic-induced disasters. Therefore, it is important for every Indonesian to possess high levels of disaster literacy and disaster preparedness to minimize losses caused, specifically for tectonic and volcanic-induced disasters. Research data are collected through offline questionnaires chosen for the size of research area and age spread of respondents that are dominated by age 36 and older respondents. Data analysis are done using SPSS 26 and multiple linear regression method is used due to multiple independent variables used in this research. Significant relationship is found between disaster literacy and emergency response plans as well as disaster literacy and early warning systems. However, significant relationship between disaster literacy and disaster knowledge as wall as disaster literacy and resource mobilizations are not present. While the researched community possess the ability to prevent excessive losses, knowledge and resources utility still needs to be maximized further.